Fraud Intention in the Indonesian Banking Industry: a Development for Fraud Diamond Theory Measurement Scale - Santoso, Ignatius Hari; Mulyo Budi Setiawan; Ali Maskur (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
This study investigates the factors that contribute to fraud intention within the Indonesian banking industry, focusing on job pressure, opportunity, rationalization, professional capacity, and job insecurity, based on the Fraud Diamond Theory. By employing a mixed-method approach, we first develop a fraud intention measurement scale through interviews and focus group discussions, followed by hypothesis testing on a sample of 100 banking employees. Findings reveal that high job pressure and job insecurity significantly influence fraudulent intentions, especially when employees perceive opportunities and rationalize fraudulent actions. These insights emphasize the need for realistic performance expectations, robust internal controls, and a supportive work environment in banks to mitigate fraud risks. This study enhances the understanding of fraud dynamics in Indonesian banks and suggests directions for future research, including a broader geographical scope and examination of corporate culture's role in fraud prevention.